A Penning trap for advanced studies with particles in extreme laser fields - Vogel, Manuel; Quint, Wolfgang; Stöhlker, Thomas (Nuclear instruments & methods in physics research. Section B, Beam interactions with materials and atoms, 2012)
We present a Penning trap as a tool for advanced studies of particles in extreme laser fields. Particularly, trap-specific manipulation techniques allow control over the confined particles’ localization and spatial density by use of trap electrodes as ‘electrostatic tweezers’ and by application of a ‘rotating wall’, respectively. It is thereby possible to select and prepare well-defined ion ensembles and to optimize the laser-particle interaction. Non-destructive detection of reaction educts and products with up to single-ion sensitivity supports advanced studies by maintaining the products for further studies at extended confinement times of minutes and above. The trap features endcaps with conical openings for applications with strongly focused lasers. We show that such a modification of a cylindrical trap is possible while harmonicity and tunability are maintained.